Competition and corporate tax evasion: An institution-based view - Gokalp, O.; Lee, S.; Peng, Mike (Pergamon, 2016)
Why do firms evade taxes? We tackle this question by studying firms in the formal sector operating in countries with different institutional backgrounds, and comparing the incentives and constraints of staying within the formal sector against the competitive pressures originating from the informal sector. We argue that it is the combination of these factors that largely explains formal firms' tax evasion decisions. Our findings highlight the dark side of competition, particularly when it originates from perceivably unfair sources (i.e. from the informal sector). We also shed light on how this effect is moderated by the institutional conditions of the environment.